Three Contemporary Poets / Thom Gunn, Ted Hughes and R. S. Thomas - Dyson A. E; Macmillan (1990)
This Casebook adopts a critical perspective towards the aims and achievements of three leading British Poets of the post-1950 period. General Editor's Preface, Introduction, Thom Gunn, Gun on Himself and Poetry, Critical Studies, Ted Hughes, Hughes on himself and Poetry, Critical Studies, R. S. Thomas, Thomas on Himself and Poetry, Critical Studies, Selected Bibliography, Acknowledgements, Index.